Climate change and water management impacts on land and water resources - Ali, Syed Mahtab (Curtin University, 2007)
This study evaluated the impacts of shallow and deep open drains on groundwater levels and drain performance under varying climate scenarios and irrigation application rates. The MIKE SHE model used for this study is an advanced and fully spatially distributed hydrological model. Three drain depths, climates and irrigation application rates were considered. The drains depths included 0, 1 and 2 m deep drains. The annual rainfall and meteorological data were collected from study area from 1976 to 2004 and analysed to identify the typical wet, average and dry years within the record. Similarly three irrigation application rates included 0, 10 and 16 ML/ha-annum. All together twenty seven scenarios (3 drains depths, 3 climates and 3 irrigation application rates) were simulated. The observed soil physical and hydrological data were used to calibrate and validate the model. Mean square error (R[superscript]2) of the simulated and observed water table data varied from 0.7 to 0.87. Once validated the MIKE SHE model was used to evaluate the effectiveness of 1 and 2 metre deep drains. The simulated water table depth, unsaturated zone deficit, exchange between unsaturated and saturated zones, drain outflow and overland flow were used to analyse their performance. The modeling results showed that the waterlogging was extensive and prolonged during winter months under the no drainage and no irrigation scenario. In the wet climate scenario, the duration of water logging was longer than in the average climate scenario during the winter months. In the dry climate scenario no waterlogging occurred during the high rainfall period. The water table reached soil surface during the winter season in the case of wet and average climate. For the dry climate, the water table was about 0.9 metres below soil surface during winter.One and 2 metre deep drains lowered the water table up to 0.9 and 1.8 metres in winter for the wet climate when there was no irrigation application. One metre deep drains proved effective in controlling water table during wet and average climate without application of irrigation water. One metre deep drains were more effective in controlling waterlogging a in wet, average and dry years when the irrigation application rate was 10 ML/ha-annum. With 16 ML/ha-annum irrigation application, 1 metre deep drains did not perform as efficiently as 2 metre deep drains in controlling the water table and waterlogging. In the dry climate scenario, without irrigation application, 1 metre deep drains were not required as there was not enough flux from rainfall and irrigation to raise the water table and create waterlogging risks. Two metre deep drains lowered the water table to greater depths in the wet, average and dry climate scenarios respectively when no irrigation was applied. They managed water table better in wet and average climate with 10 and 16 ML/ha-annum irrigation application rate. Again in the dry climate, without irrigation application 2 metre deep drains were not required as there was a minimal risk of waterlogging. The recharge to the groundwater table in the no drainage case was far greater than for the 1 and 2 metre deep drainage scenarios. The recharge was higher in case of 1 metre deep drains than 2 metre deep drains in wet and average climate during winter season.There was no recharge to ground water with 1 and 2 metre deep drains under the dry climate scenarios and summer season without irrigation application as there was not enough water to move from the ground surface to the unsaturated and saturated zones. When 10 ML/ha-annum irrigation rate was applied during wet, average and dry climate respectively, 1 metre deep drains proved enough drainage to manage the recharge into the groundwater table with a dry climate. For the wet and average climate scenarios, given a 10 ML/ha-annum irrigation application rate, 2 metre deep drains managed recharge better than 1 metre deep drains. Two metres deep drains with a 10 ML/ha-annum irrigation application rate led to excessive drainage of water from the saturated zone in the dry climate scenario. Two metres deep drains managed recharge better with a 16 ML/ha-annum irrigation application rate in the wet and average climate scenarios than the 1 metre deep drains. Two metres deep drains again led to excessive drainage of water from the saturated zone in dry climate. In brief, 1 metre deep drains performed efficiently in the wet and average climate scenarios with and without a 10 ML/ha-annum irrigation application rate. One metre deep drains are not required for the dry climate scenario. Two metre deep drains performed efficiently in the wet and average climate scenarios with 16 ML/ha-annum irrigation application rate. Two metre deep drains are not required for the dry climate scenario.